METHODS AND ALGORITHMS OF SOFT DECODING FOR SIGNALS WITHIN INFORMATION TRANSMISSION CHANNELS BETWEEN CONTROL SYSTEMS ELEMENTS - Freyman, V. I. (Radio Electronics, Computer Science, Control, 2019)
Context. The problems of increasing the reliability of information transmission in the channels of control systems against the background of the impact of a set a different nature and type interference are solved. The object of research is receiving device (channel symbols decoder), the subjects of research are models, methods and algorithms of proceeding and decision making for elementary signals (channels symbols). The goal is creation and research of methods and algorithms of elementary signals «soft» decoding for providing of information transmission reliability in the build-in and dedicated channels of control systems. Method. The math methods of fuzzy sets for description of errors within information transmission channels between control systems elements is used. The methods and algorithms of «soft» decoding within first decision device of control systems elements are realized (this methods allows get more information for decision making then «hard» method of decision making). The program simulation of proposed method of decision making based on fuzzy logic is executed. Results. The structure scheme and functioning algorithm of quasi-optimal receiver of elementary signal with original using methods of fuzzy logic for decision making are created. The algorithm of decision making is researched with using the simulation tool MathWorks Fuzzy Logic Toolbox. Conclusions. The research results allows to make the next conclusions that proposed «soft» decoding method provides greater «flexibility» for decision making that positively affects the reliability of information transmission; don’t require the introduction and use of multi-valued logic (for example, the symbol «x» for the model of the channel 2×3, the symbols «1b» and «0b» for the model of the channel 2×4, the symbols «0» ... «7» for the model of the channel 2×8) that facilitates the implementation of the decoding algorithm; allows to execute arithmetic (not logical) calculation for decreasing a computational difficult of decision making algorithm.